2016
DOI: 10.1016/j.kjms.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between primary restless legs syndrome and migraine with aura

Abstract: In this study, the prevalence and characteristics of definite migraine in primary restless legs syndrome (pRLS) patients and matched control patients (CPs) were investigated. We evaluated 63 consecutive adult pRLS patients and 141 age- and sex-matched controls in this case-control study. The diagnosis of migraine and its subtypes were defined based on The International Classification of Headache Disorders-II. Only those with "definite" migraine were included in the study. The mean age of 63 adult pRLS patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 30 publications
3
12
0
4
Order By: Relevance
“…In our study, we determined that rs2300478 in MEIS1 and rs4626664 in PTPRD increased the risk of RLS in the entire cohort; furthermore, the SNP rs4626664 in PTPRD was significantly associated with RLS in patients with MoA. Bilgehan et al 9 indicated that migraine and MA were significantly more common in patients with RLS; as in our previous study, we observed an association between the prevalence of RLS and that of migraine, especially MA. 21 We also showed that migraineurs with RLS had poor sleep quality more often than those without RLS, which corroborated our previous finding that RLS independently predicted sleep disturbance (PSQI score ≥ 6).…”
Section: Discussionsupporting
confidence: 77%
“…In our study, we determined that rs2300478 in MEIS1 and rs4626664 in PTPRD increased the risk of RLS in the entire cohort; furthermore, the SNP rs4626664 in PTPRD was significantly associated with RLS in patients with MoA. Bilgehan et al 9 indicated that migraine and MA were significantly more common in patients with RLS; as in our previous study, we observed an association between the prevalence of RLS and that of migraine, especially MA. 21 We also showed that migraineurs with RLS had poor sleep quality more often than those without RLS, which corroborated our previous finding that RLS independently predicted sleep disturbance (PSQI score ≥ 6).…”
Section: Discussionsupporting
confidence: 77%
“…4 Furthermore, the disorder is estimated to be the third most common neurological disorder as it affects 10-20% of the worldwide general population. 4,5 Even so, the pathophysiology of migraine remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified a higher prevalence of restless legs syndrome (RLS) in migraine patients. 5 RLS is classified as a neurological sensorimotor disorder with symptoms that include distressing or painful sensations in the legs, which are more frequent in the evenings and at night and are exacerbated when the body is at rest. Sleep disturbance is, therefore, the most significant clinical morbidity associated with RLS.…”
Section: Introductionmentioning
confidence: 99%
“…Heyer et al [29] are also in harmony with the higher incidence of sleep disturbances among children and adolescents with migraine which result in lowered sense of wellbeing, decreased ability to cope with the headache, impaired daytime functioning, and great negative impacts on school performance as well as attendance. Harnod et al [6] as well as Acar et al [30] recorded high incidences of malformed sleep microstructure and various types of parasomnias (sleep talking, somnambulism and bruxism) as well as increased PLMs in migraine patients which were associated with higher headache severities scores and increased disabilities caused by migraine. On the other hand, Harnod et al [6] revealed a higher incidence of subsequent migraine development in children with non-apneic sleep disorders which suggests that sleep abnormalities may prodrome the headache attacks in some patients.…”
Section: Discussionmentioning
confidence: 97%